A função educativa da policial penal: aportes para pensar a prisão como instituição social humanizada - Oliveira, Marcos Melo de (Universidade Federal de São Carlos, 2024)
This study assumes that education is a complex phenomenon, which occurs throughout life and in all places and situations. From this perspective, the prison, as an institution, is understood as a space of society that has an educational role for everyone who lives and works there. We took as a sample for this study, the criminal police officers who work in a prison unit located in the region of Triângulo Mineiro, state of Minas Gerais, Brazil. The general objective of this study is delimited: to understand the educational function of criminal police officers and unfolds into specific objectives: to map and analyze studies published between 2013 and 2023 on the work, career and duties of criminal police officers and to analyze legal regulations and daily practices in the researched unit. This is a qualitative study that uses bibliographic research, document analysis, questionnaire, conversation circles and field diary as methodological procedures. The bibliographical research offered us a field of knowledge that allowed us to build and substantiate the relevance of this study and how we could move forward: we chose, based on this theoretical foundation, to focus on women as criminal police officers: What is the educational role of criminal police officers in the prison institution? Documentary research allowed us to analyze how the Criminal Police emerged and their responsibilities at the federal and state (Minas Gerais) levels, as well as some adjustments caused by the covid-19 pandemic, in the years 2021 and 2022. As empirical data collection resources, the questionnaire as a way of approaching and characterizing the collaborators and the conversation circles that allowed us to discuss the perception of the criminal police officers about their work and role in the prison institution. In the field diaries we recorded the journey of reflections and concerns. From the organization and analysis of data, anchored in the content analysis proposed by Franco (2018), two focuses of analysis emerged: Attributions of criminal police officers and their obstacles and Meanings changed, others expanded. For analysis purposes, we established the 1st focus axes - Duties of criminal police officers and their obstacles: The big challenge within the unit is working with the teams, with the girls...; There's a little bit of almost everything missing in prison and there's no shortage of silence! In the 2nd focus - Meanings have changed, others have expanded, the axes of analysis are: The meaning that criminal police officers attribute to their relationships with people deprived of liberty and with prison; Dialogue as a working tool for criminal police officers in prison and The educational process of humanization. The results of the study show that the duties of criminal police officers, despite the workload and other obstacles they face, do not consist of simply monitoring people deprived of liberty and ensuring security in the prison institution. Some paths were announced with the expansion of our understanding built in the doctorate course, in experiences with crossing partners and in dialogue with our knowledge from our experience as a criminal police officer: lifelong education in all spaces, the transversality of actions as a powerful indication to modify this institution that insists on working backwards and hope leads us to defend the thesis: criminal police officers have relevant social value and contribute with their knowledge, anchored in dialogue and humanization, to the creation of a quality public service for people deprived of liberty and for society.
The educational function of the criminal police: contributions to thinking about prison as a humanized social institution
Keywords: Educação; Policiais penais; Pessoas em privação de liberdade; Práticas sociais; Processos educativos; Education; Criminal police; People deprived of liberty; Social practices; Educational processes; CIENCIAS HUMANAS::EDUCACAO